Model Risk Analysis of Multiplier Technology Applied at Stock Valuation of Russian Companies - V. B. Minasyan; D. G. Ivko (Финансы: теория и практика, 2019)
This work is a new direction in the authors’ previous study on applying the market multipliers in assessing the value of oil and gas companies. The work is based on the findings of statistical studies of multipliers calculated for the industry, as well as their volatility over a 12-year period — from 2006 to 2017 inclusively, as exemplified by 46 companies from nine sectors of the economy of the Russian Federation. The analysis of the risk measures Value-at-Risk (hereinafter VaR) and Expected Shortfall (hereinafter ES) was conducted by means of volatility calculated in different ways. In particular, the multiplier volatility was introduced by V. B. Minasyan. It was established that for all nine sectors of the Russian economy, calculated with conventional stock volatility statistics (when possible), risk valuation measures VaR and ES led to lower calculated risk values compared to those calculated using multiplier volatility. The results of the study are of interest to evaluators, investors and other interested parties, as it allows to analyze the general behavior of the stock value in Russian companies and to compare the change in indicators of various economic sectors in terms of multiplier technology.